PERAN KEMENTERIAN SOSIAL REPUBLIK INDONESIA BAGI MASYARAKAT MISKIN INDONESIA DI MASA PANDEMI - Evi Purnamawati (SOL JUSTICIA, 2020)
Pandemic covid-19 and government policy by issuing a government regulation no.21 year 2020 about large scale social restrictions ( psbb covid-19 ) in order to accelerate the handling, Practical demolishes all the joints the life of the people. To anticipate a weakening in the economy at the heart of communities , then the government through the ministry of social affairs , move given various the program and incentives. But each program would practice and incentives for the necessary control mechanisms and evaluation, so repair services available to the community to feel. By using the method of writing juridical, normative writers strove to unravel about whatever role and the strategies from social ministry for the poor in the, this pandemic and also to see about the effectiveness of the role and the program in practice. The hope that these words could contribute constructively for improvements in performance in the future, social ministry and also the public is getting get maximum service